Diagnostic accuracy of indocyanine green fluorescence imaging and multidetector row computed tomography for identifying hepatocellular carcinoma with liver explant correlation. Issue 12 (1st April 2017) - Masuda, Koichi; Kaneko, Junichi; Kawaguchi, Yoshikuni; Togashi, Junichi; Arita, Junichi; Akamatsu, Nobuhisa; Sakamoto, Yoshihiro; Hasegawa, Kiyoshi; Sumihito, Tamura; Kokudo, Norihiro
Abstract : Aim: Indocyanine green (ICG)‐fluorescence imaging is useful for detecting hepatocellular carcinoma (HCC) during surgery, but its accuracy has not been compared to that of multidetector row computed tomography (MDCT) with liver explant correlation. The aim of the present study was to clarify the precise diagnostic accuracy of ICG‐fluorescence imaging for detecting HCC in a whole explant liver survey. Methods: Thirty‐three patients with end‐stage liver disease (mean age, 53 years) were prospectively enrolled in the present study. The mean Model for End‐stage Liver Disease score was 14.6. One month before and 1 week prior to living donor liver transplantation, all patients underwent MDCT and administration of ICG. Following whole liver resection, the explanted liver was sliced. Gross examination and ICG‐fluorescence imaging of both sides of the cut specimen was carried out and all focal liver lesions were recorded. Results: Pathologic examination diagnosed 18 of 84 focal liver lesions as HCC. Of those, MDCT and ICG‐fluorescence imaging diagnosed 12 and 13 HCCs, respectively. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of MDCT were 66.7%, 92.4%, 70.6%, 91.0%, and 86.9%, respectively, compared with those of ICG‐fluorescence imaging at 72.2%, 31.8%, 22.4%, 80.8%, and 40.5%, respectively. Conclusion: The sensitivity of ICG‐fluorescence imaging for detecting HCC with liver explant correlation was similar to that of MDCT. However, ICG‐fluorescence imaging had low specificity in the setting of decompensated cirrhotic explant liver correlation.